Effect of pressure and supply configuration on mixing efficiency through Venturi effect for co2/h2-ch4/h2 mixtures in Power-To-Gas process: CFD analysis - Echeverri Uribe, Camilo; Mejía Botero, Cristian Camilo; Ditta Granados, Jhon Jairo; Amell Arrieta, Andrés Adolfo (Ingeniería Solidaria, 2024)
Introduction: The present article is one of the outcomes of the project “Desarrollo de un sistema “power to gas” (PTG) en el contexto de las fuentes de energía renovables y convencionales disponible en la Guajira” This project was carried out by the University of Antioquia and the University of La Guajira during the period 2019-2023. Problem: Efficiency and uniformity in gas mixing for Power-to-Gas applications are influenced by pressure variations and supply configurations. Objective: To assess the impact of pressure variations and supply configurations on the efficiency of the Venturi mixing process, utilizing indicators such as the Z-factor and the coefficient of variation (CoV). Methodology: Numerical simulations were conducted for four mixer configurations. For CO2/H2 mixtures, pressures of 1 bar (case i) and 4 bars (case ii) were considered; for CH4/H2 mixtures, pressures of 3 bars (case i) and 35 bars (case ii) were studied. Results: As the inlet gas pressure increases, uniformity decreases for both mixtures. Horizontal H2 feeding improves CO2/H2 uniformity, while vertical feeding benefits CH4/H2 mixing. The mixer reduces CoV by an average of 80% for CO2/H2. For CH4/H2 mixtures at 3 bars, there is a 60% reduction, but at 35 bars, coefficients increase by 56%. Conclusion: Pressure and supply configuration significantly influence the mixing process, underscoring the importance of considering these factors in Power-to-Gas applications. Originality: The study explores the Venturi mixing process in specific gas mixtures for Power-to-Gas applications. Limitations: The studied conditions and configurations may not encompass all possible scenarios in Power-to-Gas applications.